Partial Ear Defects - Pickrell, Brent B.; Hughes, Christopher D.; Maricevich, Renata S. (Seminars in Plastic Surgery, 2017)
Reconstruction of partial ear defects represents one of the most challenging areas within reconstructive surgery of the head and neck. Each case of auricular reconstruction is unique and warrants a systematic approach that accounts for defect size and location, the quality of the surrounding skin, patient preference, and operator experience. In this article, the authors outline different reconstructive approaches for defects of the upper-, middle-, and lower-third of the auricle. The relevant anatomy is discussed in detail. Successful outcomes in auricular reconstruction rely on the surgeon's careful analysis of the defect as well as knowledge of the different reconstructive options available.
Keywords: auricular reconstruction; ear reconstruction; partial ear defects